Kepuasan Pelanggan Terhadap Kualitas Produk Motor Honda Pada CV. Intan Prima Motor - Muhammad Awal (Musamus Journal of Business & Management is a peer-reviewed journal published by Faculty of Ecconomics and Business, Musamus University, Merauke Papua Indonesia., 2020)
This study aims to determine the partial effect of product quality on customer satisfaction CV. Intan Prima Motor Merauke. The type in this research is quantitative research, while the source of the data obtained in this study are primary data and secondary data. In this study the population is all customers who have bought a motorbike in the CV. Intan Prima Motor and by using the Slovin formula can be sampled in a study of 91 people, and also used incidental sampling techniques. The t test was done using SPSS software. The results of the research show that partially the product quality has a positive and significant effect on customer satisfaction, by improving the quality of products of this Honda type sport motorbike can provide satisfaction to consumers so that sales can increase again and the company gets the profit as expected. Keywords: Product Quality, Customer Satisfaction